PEMBANGUNAN PARIWISATA BUDAYA - ruth rinda (Institut Pemerintahan Dalam Negeri, 2018)
Cultural tourism as tourism brand in Tana Toraja on its development is not running well. The government as is considered as the umbrella of the culture in one side, is also considered had marginalized the community. The efforts to foster and develop tourism nationally are also aimed at improving the quality of the country's culture, introducing the heritage of the nation as well as natural scenery, including maritime nature in various parts of the country in Indonesia. based on this, tourism management and development needs to be improved for the community.